English as an International Language at United World College East Africa: Attitudes to native and outgroup accents: Qualitative method - Nowacka, Marta; Nowacki, Antoni (Research in Language, 2025)
This paper presents qualitative results on attitudes to English as an International Language (EIL) at a multicultural, highly diversified community of United World College East Africa, Tanzania, Moshi campus. The results reveal that nearly half of the respondents admit to preferring one native variety of English, with most of the outgroup participants expressing the wish to speak with a British or American accent. The most common ways of adjusting speaking for the benefit of communicative partners are paraphrasing, repetition and slowing down. Vietnamese, Asian English in general, and Irish turn out to be the most difficult accents to comprehend. Pronunciation is the most frequent reason for incomprehensibility. Among the ways of adjusting to accents, listening carefully and immersion are the most often used.